Nutrition capacity development: a practice framework. Issue 3 (7th May 2013) - Shrimpton, Roger; Hughes, Roger; Recine, Elisabetta; Mason, John B; Sanders, David; Marks, Geoffrey C; Margetts, Barrie
Abstract: Objective: To outline a framework and a process for assessing the needs for capacity development to achieve nutrition objectives, particularly those targeting maternal and child undernutrition. Design: Commentary and conceptual framework. Setting: Low- and middle-income countries. Result: A global movement to invest in a package of essential nutrition interventions to reduce maternal and child undernutrition in low- and middle-income countries is building momentum. Capacity to act in nutrition is known to be minimal in most low- and middle-income countries, and there is a need for conceptual clarity about capacity development as a strategic construct and the processes required to realise the ability to achieve population nutrition and health objectives. The framework for nutrition capacity development proposed recognises capacity to be determined by a range of factors across at least four levels, including system, organisational, workforce and community levels. This framework provides a scaffolding to guide systematic assessment of capacity development needs which serves to inform strategic planning for capacity development. Conclusions: Capacity development is a critical prerequisite for achieving nutrition and health objectives, but is currently constrained by ambiguous and superficial conceptualisations of what capacity development involves and how it can be realised. The current paper provides a framework to assist this conceptualisation, encourage debate and ongoing refinement, and progress capacity development efforts.